ANALISIS FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DI DESA BUKIT SEGOLER KECAMATAN TEBAS - Nurhazizah Nurhazizah; Yohanes Bahari; Rustiyarso Rustiyarso (Universitas Tanjungpura, 2022)
This study describes the factors that cause children to drop out of school and the efforts of parents to overcome school dropouts in Bukit Segoler Village, Tebas District. This type of research uses a qualitative method with a descriptive approach. The data sources for this study were children who had dropped out of junior high school and parents of children who had dropped out. The results of this study are environmental factors, the environment greatly affects children in social life, also plays a role in influencing children's thinking, and the accessibility of the distance from home to school also affects children. The proximity of children to school is related to the provision of facilities from their parents, children's interest in attending school, arising from themselves and from the environment. Parents also try hard to guide motivate, organize their children, so that children still have a strong desire to stop and not go to school anymore.